Effects of plyometric training on physical fitness attributes in handball players: a systematic review and meta-analysis - Wang, Xiaolin; Zhang, Kaiqi; Samsudin, Shamsulariffin; Hassan, Muhammad Zarif; Yaakob, Sam Shor Nahar; Dong, Delong (Journal of Sport Science and Medicine, 2024)
This meta-analysis aimed to examine the effects of plyometric training on physical fitness attributes in handball players. A systematic literature search across PubMed, SCOPUS, SPORTDis-cus, and Web of Science identified 20 studies with 563 players. Plyometric training showed significant medium-to-large effects on various attributes: countermovement jump with arms (ES = 1.84), countermovement jump (ES = 1.33), squat jump (ES = 1.17), and horizontal jump (ES = 0.83), ≤ 10-m linear sprint time (ES =-1.12), > 10-m linear sprint time (ES =-1.46), repeated sprint ability with change-of-direction time (ES =-1.53), agility (ES =-1.60), maximal strength (ES = 0.52), and force–velocity (muscle power) (ES = 1.13). No significant impact on balance was found. Subgroup analysis indicated more pronounced agility improvements in players ≤ 66.6 kg compared to > 66.6 kg (ES =-1.93 vs.-0.23, p = 0.014). Additionally, greater improvements were observed in linear sprint and repeat sprint ability when com-paring training durations of > 8 weeks with those ≤ 8 weeks (ES =-2.30 to-2.89 vs. ES =-0.92 to-0.97). In conclusion, plyometric training effectively improves various physical fitness attributes, including jump performance, linear sprint ability, maximal strength, muscle power and agility.